Endoscopic management of congenital choanal atresia: Second look is mandatory (Bangladesh Journal of Otorhinolaryngology, 2016)
Congenital choanal atresia (CA) is a rare abnormality characterized by unilateral or bilateral obstruction of the posterior end of the nasal cavity. With an incidence of 1:1000 to 1:8000 births, it is more in female than in males and unilateral more common than bilateral. Surgical procedures aim to provide adequate functional choanal patency and a low rate of rest enosis, with shorter surgery and hospitalization times, to minimize morbidity and mortality, this study done to evaluate the effectiveness and safety of endoscopic nasal surgical techniques for the treatment of congenital choanal atresia in patients with unilateral and bilateral atresia and to emphasis in the important of second look procedure at the time of removal of stent to assess the wideness of neochoana, and to remove any granulation tissue ,or polyps, it involved 13 patients, 10 with unilateral CA and 3 bilateral CA, all involved in surgery and second look.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 76-79